Introducing the Ag-Incentives Consortium and Database - Tokgoz, Simla; Laborde Debucquet, David; Lallemant, Tess; Majeed, Fahd; Martin, Will (Global Trade Analysis Project, 2017)
Prior to the 1980s, information on agricultural incentives provided by governments was extremely limited and difficult to access. Much debate took place on the basis of participants’ preferred alternative facts. During the 1980s, the OECD began to collect detailed information on agricultural incentives in member countries, but data remained fragmentary for developing countries. The only close-to-global information on agricultural distortions was provided by a one-off study undertaken by Kym Anderson at the World Bank, completed in 2009. The objective of this initiative is to bring together information on agricultural incentives from five key institutions: FAO-MAFAP; the Inter-American Development Bank; IFPRI; the OECD and the World Bank. The resulting data are presented in a consistent format at http://www.ag-incentives.org This paper will discuss the methods used and the coverage of this database, and its potential value to economic modelers.